HIV gene therapy that's not a SIN. Issue 4 (July 2010) - Lin, Min-Hsuan; Sivakumaran, Haran; Harrich, David
Evaluation of: Wang Z, Tang Z, Zheng Y et al. : Development of a nonintegrating Rev-dependent lentiviral vector carrying diphtheria toxin A chain and human TRAF6 to target HIV reservoirs. Gene Ther. (2010) (Epub ahead of print). HIV infection is incurable, but can be effectively controlled by antiviral therapy using a combination of drugs. HIV persistence during therapy is attributed to long-lived cells harboring genome-integrated HIV maintained in a transcriptionally silent state, which are refractory to current antiviral drugs. Transient and periodic activation of HIV in these cellular reservoirs leads to continual viremia. Wang et al. tackle the question of whether gene therapy using nonintegrating lentiviral vectors expressing cytotoxic proteins can specifically target HIV-infected cells. This approach has advantages since there is little chance of tumorigenesis through activation or mutation of proto-oncogenes typically associated with integrating viral vectors. These conditional vectors also express their cytotoxic payloads only in the presence of HIV and not, theoretically, in uninfected cells. As such, the vectors described by Wang et al. could be used to efficiently kill specific cellular reservoirs persistently infected with HIV.